Pertumbuhan Dan Hasil Tanaman Sawi (Brassica juncea L) Setelah Aplikasi Pupuk Hayati Tunggal Dan Dan Konsorsium - A Marthin Kalay; Reginawanti Hindersah; Abraham Talahaturuson; Riadh Uluputty; Ferra Langoi (Agrologia, 2015)
The use of biofertilizers is important to prevent the negative impact of the synthetic fertilizers in vegetable production.  This study aimed to determine the effect of single biofertilizer  Azotobacter, and consortial biofertilizer which consist of nitrogen fixer bacteria and pohosphate solubilizing bacteria on the growth and yield of green cabbage (Brassica juncea L). The experimental designed was  randomized block design with five replications. Green cabbage seedling were inoculated with biofertilizer Azotobacter and consortial biofertilizer  on the growth and yield of green cabbage. Plants with consortial biofertilizer showed better growth and yield than that received single biofertilizer. Consortial biofertilizer  can increase plant height and shoot fresh weight up to 15.68 % and 17.05 %, while those with  Azotobacter  were 7.77 % and 9.58 % consecutively, compared with plants control.